Behind the Support for Redistributive Politics: Social Preferences or Beliefs? - Pablo Bra\~nas-Garza; Antonio Cabrales; María Paz Espinosa; Teresa García-Mu\~noz (CESifo GmbH, 2024)
In this paper we explore how individual social preferences correlate with political support for redistribution. We ran an incentivized experiment with a large representative sample of the Spanish population. Our participants took six decisions that elicited their social preferences. Their choices could result in a different total surplus and different distributions of the surplus between the subject and an anonymous counterpart. In our sample, social preferences are unrelated to political support for distributive policies. The main correlates for support of redistribution are the beliefs concerning the importance of effort versus luck for success (fairness), the trust in government institutions (effectiveness) and the perceived importance of the poverty problem (need).
Keywords: C93; D31; D72; 330; elicitation of social preferences; income distribution and politics; trust in government institutions